If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying (-1 * 10(6 + -1x)) + 3x + -8 = 0 Multiply -1 * 10 (-10(6 + -1x)) + 3x + -8 = 0 ((6 * -10 + -1x * -10)) + 3x + -8 = 0 ((-60 + 10x)) + 3x + -8 = 0 (-60 + 10x) + 3x + -8 = 0 Remove parenthesis around (-60 + 10x) -60 + 10x + 3x + -8 = 0 Reorder the terms: -60 + -8 + 10x + 3x = 0 Combine like terms: -60 + -8 = -68 -68 + 10x + 3x = 0 Combine like terms: 10x + 3x = 13x -68 + 13x = 0 Solving -68 + 13x = 0 Solving for variable 'x'. Move all terms containing x to the left, all other terms to the right. Add '68' to each side of the equation. -68 + 68 + 13x = 0 + 68 Combine like terms: -68 + 68 = 0 0 + 13x = 0 + 68 13x = 0 + 68 Combine like terms: 0 + 68 = 68 13x = 68 Divide each side by '13'. x = 5.230769231 Simplifying x = 5.230769231
| 2x+27d=50 | | 3x+2-5+2x=-14 | | 6y+5+73=180 | | 0(x)=4.45x^2-75 | | 0=109000/(.12-g) | | 2x^2-25x+50=4158 | | W+3w+3=w+18 | | 4x+20y=-16whatisx | | 4x+20y=-16 | | x+y-2=6 | | 5s-3s+2=s+5 | | f(x)=9x-x^3 | | 7x+6y=108 | | 2y+23=-3(y+4) | | -3x+1=-2x-1+1 | | -2(3s-4)-8=-3(5s+5)-5 | | 20(x)=25(1) | | -2(3x-4)-8=-3(5x+5)-5 | | (3/x)*5x | | 2m+m+m+2=w+18 | | 25(1)=20(x) | | 3(x+3)-7x=5 | | 3m+5=m+9 | | 0.30(24)+0.05x=0.10(12+x) | | 0.90x+0.05(14-x)=0.10(-61) | | -4u^2+u+3=0 | | 0.8=[3.6/1][8.5/21000] | | 0.8=[DeltaQ/1][8.5/21000] | | 4+3f-2f+f=f+5 | | 4x-5=3x-(8) | | 4x+5=3x-(8) | | 4+3f-2+f=f+5 |